Odpowiedzi

2009-11-22T12:55:12+01:00
=[(-,05)*0,8-(-0,8)*0,5]/[1-(1-1/3)*(-1/3)]-(-0,2)*(-0,2)= [-0,4-(-0,4)]/[1-(2/3*(-1/3)]-0,1=(-0,4+0,4)/[1+2/9}-0,1=0/1 2/9-0,1=0-0,1=-0,1
Najlepsza Odpowiedź!
2009-11-22T12:58:51+01:00
[(-0.5)×(4/5)-(-0.8)×(10/12)]:[1-(1-(1-2/3)×(2/3-1))]-(-0.2)×(-1i1/5)=
=[(-1/2)×(4/5)-(-8/10)×(5/6)]:[1-(1-(1/3)×(-1/3))]-(-1/5)×(-6/5)=
=[(-2/5)-(-40/60)]:[1-(1-(-1/9))]-(6/25)=
=[(-2/5)-(-2/3)]:[1-(1+1/9)]-(6/25)=[(-2/5)+(2/3)]:[1-1-1/9]-(6/25)=
=[(-6/15)+(10/15)]:[-1/9]-(6/25)=[4/15]:[-1/9]-(6/25)=
=[4/15]×[-9]-(6/25)=(-12/5)-(6/25)=(-60/25)-(6/25)=-66/25=-2i16/25